2015
DOI: 10.1111/adj.12245
|View full text |Cite
|
Sign up to set email alerts
|

The shortened dental arch concept: awareness and opinion of dentists in Victoria, Australia

Abstract: Background: The occlusion of a complete dental arch is generally desirable but not necessary nor always achievable in many individuals. It is, however, relevant for dentists to consider what minimum number of teeth is required by individuals for oral function. This study investigated dentists' awareness and opinion of the shortened dental arch (SDA) concept in an Australian context. Methods: A self-administered voluntary and anonymous questionnaire was mailed to a sample of 434 dentists, randomly selected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 27 publications
13
23
2
Order By: Relevance
“…14 The reason behind this difference in findings may be specialists are more active in updating their knowledge through continuing dental education programme, workshops and seminars Findings in this study showed that teaching and clinical experience was not associated with level of knowledge of SDA. This was different from the study done on Sudan dentist 11 and Australian dentist 15 in which recent graduates were more aware of the concept than those who graduated 20 years before. This may be due to rapid growth in information technology and networking and seminars, workshops etc.…”
Section: Discussioncontrasting
confidence: 85%
“…14 The reason behind this difference in findings may be specialists are more active in updating their knowledge through continuing dental education programme, workshops and seminars Findings in this study showed that teaching and clinical experience was not associated with level of knowledge of SDA. This was different from the study done on Sudan dentist 11 and Australian dentist 15 in which recent graduates were more aware of the concept than those who graduated 20 years before. This may be due to rapid growth in information technology and networking and seminars, workshops etc.…”
Section: Discussioncontrasting
confidence: 85%
“…Previous studies have suggested that the SDA concept is particularly indicated for certain groups of people: middle‐aged and elderly individuals with limited possibilities for complex restorative treatment; patients in high‐risk groups; and subjects who are prone to caries, periodontal disease and tooth loss. One of the reasons for this suggestion is that older adults with reduced dexterity and reduced ability to maintain good oral hygiene may be disadvantaged by complex fixed prostheses or PRDPs that replace missing molars.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults and individuals with fewer teeth, dentists often must consider whether replacement of the lost dentition is necessary. If no treatment is provided, as an alternative, dentists should consider the minimum number of teeth required for the individual to have satisfactory oral function along with acceptable aesthetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is appropriate at this point to discuss the concept of the shortened dental arch as described by Kayser where a minimum of four occlusal units are present which can provide functional satisfaction to older adults with sufficient adaptive capacity. Other reviews have suggested that in general there are no clinically significant differences between subjects with shortened dental arches of three to five occlusal units regarding variables such as masticatory ability, signs and symptoms of temporomandibular disorders, migration of remaining teeth, periodontal support, and oral comfort. Despite the acceptance of the shortened dental arch concept by the majority of dentists, it is not widely practised.…”
Section: Management Of Compromised and Questionable Teethmentioning
confidence: 99%